Growth and Performance of Small Scale Industries in India: Exploring the Evolution and Diversification of Small Scale Industries in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The small sector in India has progressed from the production of consumer goods to the manufacture of many sophisticated and precision products like electronics control system, micro ware components, and electro-medical equipments.